2011
DOI: 10.4251/wjgo.v3.i4.49
|View full text |Cite
|
Sign up to set email alerts
|

Markers of bile duct tumors

Abstract: Biliary tract carcinomas are relatively rare, representing less than 1% of cancers. However, their incidence has increased in Japan and in industrialized countries like the USA. Biliary tract tumors have a poor prognosis and a high mortality rate because they are usually detected late in the course of the disease; therapeutic treatment options are often limited and of minimal utility. Recent studies have shown the importance of serum and molecular markers in the diagnosis and follow up of biliary tract tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 142 publications
0
22
0
Order By: Relevance
“…Mucins are glycosylated proteins that are normally expressed in the ductal and glandular epithelium of epithelial tissues [17]. The use of MUC 5 Ac (serum mucin) has been studied as a marker for bile duct cancer and as a diagnostic method and, in some cases, as a prognostic evaluation [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Mucins are glycosylated proteins that are normally expressed in the ductal and glandular epithelium of epithelial tissues [17]. The use of MUC 5 Ac (serum mucin) has been studied as a marker for bile duct cancer and as a diagnostic method and, in some cases, as a prognostic evaluation [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Markers such as p53, bcl-2, bax, S100A4, mesothelin, COX-2, P-cadherin, Dpc4/ SMAD4, topoisomerase IIa, cdc2/p34, fascin, 14-3-3s, and MUC mucins are among those that have been previously tested to show variable sensitivity and specificity. [6][7][8][9][10][11][12][13][14] Our recent study has shown that combined use of the insulin-like growth factor-II mRNA binding protein-3 (IMP3), S100P, and the von Hippel-Lindau gene product (pVHL) as an immunohistochemical panel is valuable in the detection of adenocarcinoma in bile duct biopsies. 15 By examining 72 histologically well-characterized endoscopic bile duct biopsies (40 malignant, 32 benign/reactive), we found that bile duct adenocarcinoma frequently showed an IMP3-positive/S100P-positive/pVHL-negative staining pattern, followed by an IMP3-negative/S100P-positive/ pVHL-negative pattern.…”
mentioning
confidence: 99%
“…CEA, a highly glycosylated cell surface glycoprotein, is considered a colon-specific oncofetal protein 5 and is often found in patients with malignant tumors of the digestive system such as stomach, colon, biliary tract, and pancreas cancer. 11 In the current case, neoplastic cells were negative for CEA, whereas, in human medicine, this marker shows a high sensitivity and specificity for cholangiocarcinoma. 13,14 As the inner control was also negative for both CEA and TTF1, it was concluded that these human antibodies do not react with llama biliary and pulmonary epithelium.…”
Section: Panopticmentioning
confidence: 98%